4(q-8)+6=3(q+6)-q

Simple and best practice solution for 4(q-8)+6=3(q+6)-q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(q-8)+6=3(q+6)-q equation:


Simplifying
4(q + -8) + 6 = 3(q + 6) + -1q

Reorder the terms:
4(-8 + q) + 6 = 3(q + 6) + -1q
(-8 * 4 + q * 4) + 6 = 3(q + 6) + -1q
(-32 + 4q) + 6 = 3(q + 6) + -1q

Reorder the terms:
-32 + 6 + 4q = 3(q + 6) + -1q

Combine like terms: -32 + 6 = -26
-26 + 4q = 3(q + 6) + -1q

Reorder the terms:
-26 + 4q = 3(6 + q) + -1q
-26 + 4q = (6 * 3 + q * 3) + -1q
-26 + 4q = (18 + 3q) + -1q

Combine like terms: 3q + -1q = 2q
-26 + 4q = 18 + 2q

Solving
-26 + 4q = 18 + 2q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2q' to each side of the equation.
-26 + 4q + -2q = 18 + 2q + -2q

Combine like terms: 4q + -2q = 2q
-26 + 2q = 18 + 2q + -2q

Combine like terms: 2q + -2q = 0
-26 + 2q = 18 + 0
-26 + 2q = 18

Add '26' to each side of the equation.
-26 + 26 + 2q = 18 + 26

Combine like terms: -26 + 26 = 0
0 + 2q = 18 + 26
2q = 18 + 26

Combine like terms: 18 + 26 = 44
2q = 44

Divide each side by '2'.
q = 22

Simplifying
q = 22

See similar equations:

| 4.8x+9.6= | | 5(2)-3y=6 | | 8(2.4x+1.2)= | | 5(-2)-3y=6 | | 5(0)-3y=6 | | -r+2r=4 | | 2logx=x-2 | | 0=x+4x | | 3(2x-1)=12x+10 | | 13=6x+3-2 | | 3.2=x+1.3 | | 14=4b-5+3 | | 2x*3=3x-4/3 | | 7(x+4)=-4 | | 1+2p+p=-8 | | -9(2p+4)=3(-6p-12) | | 2x^4+18=20x^2 | | 8/9x6 | | Abx=c | | -2/e=3 | | 72*7= | | Bc=ac | | 16h=(2h-10) | | 2x+5y+1x+3y=1445 | | -7265+185t=-12790 | | 1/2×(2x-6)=14 | | 4w+12=44 | | 14x/-28y-1 | | 6x+16=15x-38 | | 10n-27-3n=190 | | -5(0.2x+1.4)=27 | | .003x+.01=.0005x-.008 |

Equations solver categories